(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides information on effective lesson and teaching organization. Particular emphasis is placed on the classroom format, reflecting views on student engagement and organizational structure